2016
DOI: 10.1007/s00232-016-9882-5
|View full text |Cite
|
Sign up to set email alerts
|

Apamin-Sensitive Small Conductance Calcium-Activated Potassium Channels were Negatively Regulated by Captopril in Volume-Overload Heart Failure Rats

Abstract: In heart failure (HF), the malignant arrhythmias occur frequently; a study demonstrated that upregulation of I KAS resulted in recurrent spontaneous ventricular fibrillation in HF. However, the regulation of SK channels was poorly understood. The activation of SK channels depended on [Ca(2+)]i and PP2A; studies suggested that angiotensin II can regulate them. So, we hypothesized that in HF, the excess of angiotensin may regulate the SK channels and result in the remodeling of SK channels. To test the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…have reported that the EC 50 of the SK channel in rat ventricles is 0.23–0.59 μ m (Hongyuan et al . ). Chang et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…have reported that the EC 50 of the SK channel in rat ventricles is 0.23–0.59 μ m (Hongyuan et al . ). Chang et al .…”
Section: Methodsmentioning
confidence: 97%
“… b ; Hongyuan et al . ), which would profoundly shorten APD. We have chosen a range of g sk more conservatively (from 0.4 to 4 μS μF −1 ), based on apamin effects on APD.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR assay of SK2 was performed in the same way as in a previously described study ( 13 ). For quantification of SK2 mRNA levels, total RNA was extracted via homogenization with TriReagent (Ambion, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative PCR was performed as described previously by us. 33 Specific primer sequences of collagen I used for real‐time PCR were as follows: Collagen1, forward: 5′‐AAACCCGAGGTATGCTTGATCTGTA‐3′, reverse: 5′‐GTCCCTCGACTCCTACATCTTCTGA‐3′; Collagen Ⅲ, forward: 5′‐ACGTAAGCACTGGTGGACAG‐3′, reverse: 5′‐CAGGAGGGCCATAGCTGAAC‐3′; β‐actin, forward: 5′‐ACCCTGAAGTACCCCATGCAG‐3′, reverse: 5′‐ACATGATCTGGGTCATCTTGTGC‐3′. The relative level of mRNA was calculated by normalizing to β‐actin, according to the 2 −ΔΔ CT method.…”
Section: Methodsmentioning
confidence: 99%